The Impact of a Digital Influencer to the Purchase Decision - Maria Francisca Lies Ambarwati; Herlina Damaryanti; Harjanto Prabowo; Muhammad Hamsal (Institut Teknologi Sepuluh Nopember, 2019)
ong the many marketing tools which has given a wide range and easy accessibility. One kind of eWOM is digital influencer who uses the social media platforms such as YouTube, Instagram, Facebook. The digital influencer has a role as a communicator who influences the purchase decision of the viewers. The purpose of this study is to investigate the impact of a beauty vlogger to the purchase intention of the viewers in the YouTube channel. This study uses quantitative research method with analysis techniques include tests of validity, reliability, normality, linearity, simple linear regression, statistic descriptive, and determination. Data analysis was defined by the total quota sampling technique. Data collection was done by distributing questionnaires to 100 respondents who were the viewers of the YouTube video blog. The result of this study shows that the contribution of the digital influencer to the decision of purchasing cosmetic products is 87.6%. This result opens the opportunity to producers of life-style products to collaborate with the beauty vloggers to advertise their products.